Peran Guru dalam Membangun Toleransi dan Menangkal Intolerasi di Kalangan Siswa [The Role of Teachers in Building Tolerance and Countering Intolerance among Students] - Theresiana Debora; Yanuard Putro Dwikristanto (Universitas Pelita Harapan, 2024)
Indonesia is a country with a diverse society. Diversity can bring conflict to society, but tolerance is essential to maintaining it. Education is a key starting point for fostering tolerance. This requires teachers to carry out their role in instilling moral values in society based on the correct philosophical foundation. As the image and likeness of God, despite having fallen into sin and experiencing severe damage, humans still have a will and mind that is the basis for humans to be both tolerant and intolerant. This article aims to explore the philosophical role of Christian teachers as mentors, examining how they foster tolerance and intolerance in the classroom. The method used in writing is a literature review. The conclusion is that Christian teachers can use tolerant and intolerant attitudes correctly in the classroom through motivation, spontaneous advice with love, examples of Christ's love, and classroom habits that teach students to love each other and appreciate the work of others while hating sin.BAHASA INDONESIA ABSTRACT:Indonesia adalah negara dengan masyarakat yang beragam. Keberagaman ini sering kali menimbulkan konflik di masyarakat. Namun, toleransi merupakan hal yang penting untuk menjaga keberagaman, yang dapat dimulai dari dunia pendidikan. Hal ini menuntut guru untuk menjalankan perannya dalam menanamkan nilai-nilai moral dalam masyarakat dengan berlandaskan pada landasan filosofis yang benar. Sebagai gambar dan rupa Allah, meskipun telah jatuh ke dalam dosa dan mengalami kerusakan yang parah, manusia masih memiliki kehendak dan pikiran yang menjadi dasar bagi manusia untuk bersikap toleran dan intoleran dengan benar. Artikel ini bertujuan untuk memberikan gambaran mengenai peran guru Kristen sebagai pembimbing dalam menumbuhkan sikap toleransi dan intoleransi di dalam kelas secara filosofis. Metode yang digunakan dalam penulisan adalah tinjauan pustaka. Kesimpulan yang diperoleh adalah guru Kristen dapat menggunakan sikap toleran dan intoleransi dengan benar di dalam kelas melalui motivasi, nasihat spontan dengan kasih, teladan kasih Kristus, dan kebiasaan di dalam kelas yang mengajarkan siswa untuk saling mengasihi dan menghargai karya orang lain serta membenci dosa.